Kolaboratif Kepemimpinan dan Guru Dalam Pembentukan Sekolah Berkarakter Melalui Literasi Era Digital - Lebang, Rita; Azainil, Azainil (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This research aims to explore the application of character education in a digital context at the Islamic Center Elementary School Samarinda. The main focus is to understand the interaction between school leadership and teachers, student moral development, technology literacy, and technology use policies in the school environment. The research method uses a qualitative approach with case studies in the school. Data was collected through literature studies using digital sources such as Google Scholar and through in-depth interviews with principals, teachers, students, and parents. Data analysis was carried out by data reduction, data presentation, and data triangulation approaches to ensure the validity of the findings. The results of the study show that effective collaboration between school leadership and teachers is very important in shaping a moral school culture. Digital literacy serves as a tool to strengthen the formation of students' character, by integrating values such as integrity, responsibility, and critical thinking skills in the use of technology. In conclusion, the implementation of character education in the digital era requires close cooperation between school leadership and teachers as well as digital literacy that supports the formation of students' character in facing challenges and opportunities in the digital era. Keywords: Collaboration, Leadership, Teachers, Digital era